PERISTILAHAN AKTIVITAS MENYADAP KELAPA DALAM BAHASA MELAYU DIALEK SAMBAS - yarso, Wawan; Heryana, Nanang; Muzammil, Ahmad Rabi?ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The researcher chooses terminology as the focus of this research since terminology is a common thing in linguistic field. Menyadap Kelapa is becoming the object of this research because it has meaning that can be semantically investigated. The problems of this research are the inventory as well as lexical and cultural meaning. The purpose of this research is to describe the related problems. Significance of this research is for enriching the knowledge of both lexical and cultural meaning in linguistic field. This research is a descriptive research. The form of this research is qualitative descriptive. The source of the data is the activity of menyadap kelapa in Sambas Malay Dialect while the data is both lexical and cultural meaning. The technique of data collecting is conversing technique. The phases are inducing, interviewing, recording and noting. The result of the analysis of Terminology in Activity of Menyadap Kelapa in Sambas Malay Dialect is that; there are 43 lexical meanings including tools, materials, and activities. Cultural meanings consist of four kinds including myths and Pantang Larang. The findings of the research is hoped to be empowered in learning at school particularly as a supplementary material and media of Indonesian language lesson which are procedural and descriptive text. Keywords: Menyadap Kelapa, Sambas Malay dialect, Terminology